Ignacy Daszyński a kwestia oświaty robotniczej w dwudziestoleciu międzywojennym - Nartonowicz-Kot, Maria (Acta Universitatis Lodziensis. Folia Historica, 2001)
Ignacy Daszyński - a distinguished Polish socialist, prime minister o f the first people’s government in Lublin and later the president of the Polish Seym of 2nd tenure, was also famous for his activity in the field of the political and cultural education of the people. He believed that „only a proletarian aware of his tasks could be a maker of the new deal” - still that aim should be achieved by his educational and cultural activity. Daszyński became an initiator and a founder of the powerful, cultural-educationally, workers organisation: Towarzystwo Uniwersytetu Robotniczego (The Association of the University of Workers - TUR) and than he supervised it till beginning of 1930s. The status of the Association designed the rich programme of its activity in which the need of the various forms of the work and of its attractiveness was specially underlined. Those steps aimed to gain the support of the workers class for the Association. The action was quite successful. Till the beginning of 1930s the ranks of members (mostly the workers) and the number of units of the Association augmented. A dominant influence of I. Daszyński on TUR could be clearly observed also in the fact that since the beginning of 1930s the main slogan promoted by the Association was „education no revolution” . Still the changes of the geopolitical circumstances and the political tension in Poland forced the leaders of TUR to introduce certain modification of the ideological programme of that institution. Therefore due to I. Daszyński there was built the organisation that contributed very much to the process of the creation of the proletariat consciousness. It fulfilled an important educational mission among the workers both teaching and amusing them.